Analysis of the current situation and influencing factors of internal perceptions in patients with chronic heart failure at the county level - Ming Yu; Jiahong Ge; Lili Jiang; Rong Tang; Jing Ji; Dandan Gu; Suping Cai; Dawei Zhu; Jiaojian Shi; Shuangfeng Chen; Wenjuan Zhou; Ronghui Geng; et al. (Frontiers in Psychology)
AimThe objective of this study is to investigate interoceptive awareness—defined as the ability to perceive and interpret bodily signals—in individuals diagnosed with chronic heart failure, along with the factors that may influence this awareness. This research aims to establish a theoretical foundation for the development of psychoeducational programs focused on interoception, such as mindfulness-based symptom awareness training, and digital health interventions specifically designed for patients with chronic heart failure (CHF).MethodsA total of 406 patients diagnosed with congestive heart failure were selected as research subjects through convenience sampling from the cardiology departments of six county hospitals in Nantong City, during the period from January 2025 to March 2025. Cross-sectional surveys were conducted using various instruments, including general information questionnaires, the Multidimensional Internal Perception Assessment Questionnaire, the Social Support Scale, the Self-Rating Depression Scale, and the Memorial Heart Failure Symptom Assessment. To identify the factors influencing internal perception among CHF patients, both univariate and multivariate linear regression analyses were employed.ResultsThe overall score of the Multidimensional Assessment of Interoceptive Awareness 2C (MAIA-2C) for individuals diagnosed with congestive heart failure was recorded at 108.44 ± 15.93, within a scale range of 31–155, indicating a moderate-to-high degree of internal perception. A multivariate linear regression analysis identified several independent factors that significantly influence internal perception among CHF patients. These factors include place of residence, the frequency of hospitalizations due to heart failure in the past year, body mass index, levels of depression, availability of social support, and symptom burden.ConclusionThe internal perception ability of patients with congestive heart failure is influenced by various factors, including their residential environment, the number of hospitalizations related to heart failure in the past year, body mass index, levels of depression, the availability of social support, and symptom burden. In clinical settings, it is essential to consider the level of internal perception among patients. Furthermore, tailored intervention strategies should be developed, taking into account these influencing factors, in order to improve patients’ self-management skills and overall quality of life.